Prevalence of back pain and risk factors among bus drivers in Kelantan Darul Naim, 1995 - Azmi Hassan,; K.G. Rampal, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross sectional study was conducted to determine the prevalence of back pain among the bus drivers and office workers in a Bus company in Kelantan for the year 1994. A total of 321 employees from 350 employees were interviewed. This includes 241 bus drivers and 80 office workers who were interviewed With the use of questionnaire. From this study the prevalence of back pain among the express bus drivers was 50.8%, short distance bus driver was,60.8% and among office worker was 41.3%. For the three groups most back pain was mild (64.3%, 39.8% and 87,.0% ,respectively ). Moderate back pain occured in 28.6% of express bus drivers, 39.8% of short distance bus drivers and 12.1 % of office workers. The prevalence of severe back pain was found to be more in short distance bus drivers( 20.5% ) compared with express bus drivers and office workers (20.5%, 7.1% and 0.0%, respectively).hl three groups most subjects had low back pain (42.9%, 25.3% and 48.5%, respectively). However majority of short distance bus drivers were found to experience low back pain, neck pain and mid back pain together (32.2%). The prevalence of back pain among bus drivers was significantly associated with an uncomfortable seat (X2=23.3 d.f=2, p<0.05). The mean duration of time spent driving per day was significantly different for drivers with back pain as compared to drivers without back pain (9.1 ± 2.9 hours as compares to 8.3 ± 1.8). There was a significant association between prevalence of back pain and time spent on driving (X2=7.1 d.f =2 ,P<0.05). The mean distance of driving for drivers with back pain was not statistically different (p >0.05) as compared to drivers without back pain (302.0 ± 133.4 km as compared to 277.7 ± 136.0 km).